Pengaruh Model Pembelajaran Biologi Berbasis Probing Prompting terhadap Hasil Belajar Peserta Didik di SMA Negeri 1 Siberut - Ardi Ardi; Maria Parencia Yurike (ISLAMIKA, 2023)
The biology learning process shows that the learning outcomes of students are still low. This can be seen from the daily biology test scores of students who completed the 4 classes, namely class XI MIA1 only 19%, class XI MIA2 only 12%, class XI MIA3 only 20% and class XI MIA4 only 14%. It can be seen that teachers still use lecture and discussion methods. The purpose of this study was to determine the effect of the Probing Prompting-based biology learning model on student learning outcomes at SMAN 1 Siberut Selatan. The method used in this study was a quasi-experimental method with a Randomized Control Group Posttest Only Design. The population is all students of class XI MIA SMAN 1 Siberut Selatan and the sample is taken using the Cluster Random Sampling technique. Class XI MIA2 as the experimental class and class XI MIA3 as the control class. The research data collection instruments and techniques consisted of student activity observation sheets and learning achievement tests. The results of the analysis of research data obtained that the average value of the experimental class was 71.23 and the average value of the control class was 63.20. Data analysis using the Mann-Whitney U test is Asymp. Sig. (2-tailed) of 0.014 <0.05 then H1 is accepted and the hypothesis is accepted.